Periodic pulse train conformation based on the temporal Radon-Wigner transform - Cuadrado Laborde, Christian (2007)
By using the Radon–Wigner transform (RWT), we analyze the temporal selfimaging or Talbot effect for producing well-conformed pulse trains with variable repetition rates and duty-cycles. The relationships linking the selfimaging conditions with the fractional orders of the RWT are first obtained for unchirped pulse trains. Then, we extend the analysis to chirped pulse sequences by deriving the conditions to be fulfilled by an equivalent unchirped pulse train producing the same selfimage irradiances. This result becomes relevant for observing well-defined high order fractional selfimaging, which are of interest due to their repetition rate multiplication. Besides, the effect of the finite extension of the pulse train on the selfimage quality is analyzed and a condition is found for relating the required minimum pulse number with the chirp parameter of the pulses.